2017
DOI: 10.1103/physrevfluids.2.022801
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nonlinear sloshing induced by wetting dynamics

Abstract: Back-and-forth oscillations of a container filled with fluid often result in spilling as the gravest mode gets excited, a well-known phenomenon experienced in everyday life and of particular importance in industry. Our understanding of sloshing is largely restricted to linear response, and existing extensions mostly focus on nonlinear coupling between modes. Linear theory is expected to correctly model the dynamics of the system as long as the amplitude of the mode remains small compared to another length scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although the study of sloshing is almost two centuries old [1], it is still extremely challenging to predict the surface deformation of a container undergoing back-and-forth oscillations. The main source of difficulties is nonlinearities, which must be taken into account starting from very small amplitudes: The experiments of Cocciaro et al [2,3] have proved that the first nonlinearity to occur corrects the dissipation, and it has been recently demonstrated that, in perfect wetting, this effect becomes sizable when the sloshing amplitude compares to the thickness of the boundary layers (a fraction of millimetre in everyday life containers) [4]. This explains why, whereas natural frequencies are experimentally found in good agreement with linear sloshing theory [2,3,[5][6][7], damping rates involve larger discrepancies [2,[5][6][7].…”
mentioning
confidence: 99%
“…Although the study of sloshing is almost two centuries old [1], it is still extremely challenging to predict the surface deformation of a container undergoing back-and-forth oscillations. The main source of difficulties is nonlinearities, which must be taken into account starting from very small amplitudes: The experiments of Cocciaro et al [2,3] have proved that the first nonlinearity to occur corrects the dissipation, and it has been recently demonstrated that, in perfect wetting, this effect becomes sizable when the sloshing amplitude compares to the thickness of the boundary layers (a fraction of millimetre in everyday life containers) [4]. This explains why, whereas natural frequencies are experimentally found in good agreement with linear sloshing theory [2,3,[5][6][7], damping rates involve larger discrepancies [2,[5][6][7].…”
mentioning
confidence: 99%
“…Axisymmetric surface waves have been routinely studied in the past. Indeed, the behavior of standing waves in a circular basin is of primary interest, in particular to the study of sloshing in cylindrical tanks or harbor oscillations [14,15]. Experiments in large-scale basins were also reported in which converging axisymmetric gravity waves are generated by several wavemakers, driven in unison, surrounding the tank [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The free surface instabilities can be either be intensified or reduced, depending on a number of ambient conditions. Some experimental work on sloshing of a liquid close to its critical point has been done [275]. However, how the impact loads would be affected in such a situation, remains to be experimentally investigated.…”
Section: Discussionmentioning
confidence: 99%